INTERVAL TYPE-2 FUZZY DYNAMIC NETWORK DATA ENVELOPMENT ANALYSIS WITH UNDESIRABLE OUTPUTS CONSIDERING DOUBLE FRONTIERS: AN APPLICATION TO IRAN AIRPORTS’ SUSTAINABILITY EVALUATION - Olfat, Laya; pishdar, mahsa (International Journal of Industrial Engineering: Theory, Applications and Practice, 2018)
The sustainable airports play irrefutable role in making transportation systems sustainable. One of the approaches that can be used for evaluating airports’ sustainability is fuzzy data envelopment analysis (DEA). Fuzzy DEA methods have been introduced to cope with fuzziness of variables. However, it is noteworthy that fuzzy DEA is still restricted to fuzzy variables, while some of these variables are affected by uncertainty and also information granularity. Interval type-2 fuzzy sets which have characteristics of type-2 fuzzy sets and do not add any complexity to the calculation process can be applied to deal with such a problem. That is why in this paper, it is explored that how an extension of fuzzy dynamic network DEA approach based on double production frontiers helps to measure airports’ sustainability. Such an integrative approach in DEA approach is unprecedented. So, this extension of DEA is valuable from both technical and conceptual aspects.